Study of anti-inflammatory, analgesic and antipyretic activities of seeds of Hyoscyamus niger and isolation of a new coumarinolignan - Begum S.; Saxena B.; Goyal M.; Ranjan R.; Joshi V.B.; Rao C.V.; Krishnamurthy S.; Sahai M. (My University, 2025)
A chemical and biological validation of the traditional use of Hyoscyamus niger seeds as anti-inflammatory drug has been established. The methanolic extract of seeds of H. niger (MHN) was evaluated for its analgesic, anti-inflammatory and antipyretic activities in experimental animal models at different doses. MHN produced significant increase in hot plate reaction time, while decreasing writhing response in a dose-dependent manner indicating its analgesic activity. It was also effective in both acute and chronic inflammation evaluated through carrageenin-induced paw oedema and cotton pellet granuloma methods. In addition to its analgesic and anti-inflammatory activity, it also exhibited antipyretic activity in yeast-induced pyrexia model. Furthermore, the bioactive MHN under chemical investigation showed the presence of coumarinolignans as major chemical constituent and yielded a new coumarinolignan, cleomiscosin A methyl ether (1) along with four known coumarinolignans, cleomiscosin A (2), cleomiscosin B (3), cleomiscosin A-9′-acetate (4) and cleomiscosin B-9′-acetate (5). The structure elucidation of 1 was done by spectroscopic data interpretation and comparative HPLC analysis. Cleomiscosin A, but not its isomer cleomiscosin B, reduced dry and wet weight of cotton pellet granuloma in mice. This suggests that cleomiscosin A is an important constituent of MHN responsible for anti-inflammatory activity. © 2009 Elsevier B.V. All rights reserved.